2020
DOI: 10.1186/s12864-020-07076-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of AP2/ERF transcription factors in sugarcane (Saccharum spontaneum L.)

Abstract: Background APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF) transcription factors play essential roles in plant growth, development, metabolism, and responses to biotic and abiotic stresses. However, few studies concerning AP2/ERF genes in sugarcane which are the most critical sugar and energy crops worldwide. Results A total of 218 AP2/ERF genes were identified in the Saccharum spontaneum genome. Phylogenetic analysis showed that these genes could be divided into four groups, including 43 AP2s, 160 ERFs and De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 72 publications
7
46
0
Order By: Relevance
“…Our study demonstrated the occurrence of tandem duplications in oil palm for the expansion of all AP2/ERF family members during evolution. These results also agreed with previous findings of the tandem duplications of AP2/ERF members in Saccharum spontaneum L. [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study demonstrated the occurrence of tandem duplications in oil palm for the expansion of all AP2/ERF family members during evolution. These results also agreed with previous findings of the tandem duplications of AP2/ERF members in Saccharum spontaneum L. [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…AP2/ERF superfamily genes act as vital regulators for governing various physiological and stress responses in a wide range of plants [ 25 , 26 , 27 , 28 , 29 , 30 ]. Few genome-wide studies have been carried out to identify AP2/ERF family members in plant genomes [ 4 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. To date, no genome-wide studies have been conducted to explore the structure and role of AP2/ERF family genes in oil palm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been used to study smut infection response 19 , 20 , vital genes involved in cellulose and lignin biosynthesis 21 , plant growth-promoting rhizobacteria inoculation response 22 , and water, salt, and cold stress response 23 25 in cultivated sugarcane. Transcriptome sequencing has also been extensively applied to study gene expression changes in S. spontaneum in response to drought stress 26 , 27 , cold damage 28 31 , and identification of transcription factors 32 .…”
Section: Introductionmentioning
confidence: 99%